Performance of Computed Tomography Angiography Before Revascularization Is Associated With Higher Amputation-Free Survival in Rutherford IIb Acute Lower Limb Ischaemia - Saphir, Ebba; Svensson-Björk, Robert; Acosta, Stefan (Frontiers in Surgery, 2021)
Background: Acute lower limb ischaemia (ALI) with motor deficit (Rutherford IIb) needs urgent revascularization to avoid major amputation and mortality. It is unclear whether immediate revascularization without performing computed tomography angiography (CTA) prior to revascularization in Rutherford IIb ALI are associated with better outcomes. Methods: Retrospective observational study of Rutherford IIb ALI patients treated between 2006 and 2018. A propensity score adjusted analysis was performed to compare outcomes after performance of CTA examination or not. Results: Among 681 patients, 260 had Rutherford IIb ALI. CTA prior to revascularization was performed in 131 (50.4%) and increased (p<.001) throughout the study period. Open vascular and endovascular surgery first was performed in 147 (56.5%) and 113 (43.5%) patients, respectively. The proportion of endovascular treatment increased and open vascular surgery decreased during the study period (p=.031). In the propensity score adjusted analysis, performance of CTA was associated with decreased risk of combined major amputation/mortality (Odds ratio 0.52, 95% confidence interval 0.27-0.99; p=.046) at 1 year. Conclusion: Performance of CTA was associated with a higher amputation-free survival in revascularized patients with Rutherford IIb ALI. CTA seem to provide guidance in selecting the most appropiate candidates for revascularization and choice of technique.